ANALISIS BIAYA DAN VOLUME LABA JANGKA PENDEK PADA UMKM ANGKRINGAN 3.12 - Ari Putro, Eko Wantoro; Milanda, Dzaki; Aulia H, Lyra Nur; Aiman N, Andre (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the cost structure and short-term profit potential of the Angkringan 3.12 MSME, focusing on the products Nasi Kucing, Gorengan, and Beverages. The primary goal of this research is to assess the efficiency of cost management and each product’s contribution to net profit through the identification of fixed and variable costs, as well as calculations of contribution margin, break-even point, and margin of safety. The results indicate that the cost structure in this MSME is effectively managed, with the largest expenses allocated to main raw materials, specifically rice and cooking oil, which significantly impact total production costs. The contribution margin analysis reveals that the Beverage product has the highest contribution margin ratio of 30%, followed by Gorengan at 16.00% and Nasi Kucing at 11.67%, indicating each product’s varying contributions to the company’s profit. The break-even calculation shows that Nasi Kucing requires a minimum sale of 6,000 units, Gorengan 5,000 units, and Beverages 2,500 units to cover fixed costs, reflecting different efficiency levels among the products. Furthermore, the average margin of safety of IDR 4,333,333 or 46.67% demonstrates that Angkringan 3.12 MSME is in a financially secure position to handle market fluctuations. With efficient cost management, operational efficiency, and well-planned marketing strategies, this MSME has strong potential to enhance profitability and ensure business sustainability in the future.